2014
DOI: 10.1002/art.38818
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of the Transcription Factor Fli‐1 in Murine Lupus Development by Regulation of Interleukin‐6 Expression

Abstract: Objective The Fli-1 transcription factor is implicated in the pathogenesis of systemic lupus erythematosus (SLE) in both human patients and animal models. Dysregulation of interleukin 6 (IL-6) is also associated with SLE. We investigated whether Fli-1 directly regulates the expression of IL-6. Methods Sera were collected from wild-type and Fli-1 heterozygous (Fli-1+/−) MRL/lpr mice and the concentration of IL-6 was measured by ELISA. Expression of IL-6 in the kidney was measured by real-time PCR. T cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 47 publications
0
48
0
Order By: Relevance
“…Other prime TF candidates include TFs previously implicated in Tmem regulation such as RUNX3, E2F2, LEF1, BCL6, or members of the ELF-, KLF-, or FOXJ-families, as well as CREB1, ETS-1, and JUN-FOS, which are known to be involved in multiple cellular processes of differentiation and activation. Additional interesting candidates include (1) the aryl hydrocarbon receptor, AHR, which has been implicated in differentiation of CD4 + T cells into pro-or anti-inflammatory subsets and, hence, to modulate autoimmune diseases in various animal models (reviewed in Esser et al, 2009;Hanieh, 2014) and (2) the ets-family member FLI-1, which has been reported to affect thymic T cell development, TCR signaling, glycosphingolipid metabolism, and cytokine expression and has been implicated in autoimmune diseases, too (Richard et al, 2013;Sato et al, 2014). Others of the top-predicted TFs have not been directly associated to regulation of Tmem differentiation yet, but are players in potentially relevant cellular processes, such as intracellular signaling (RFX3, via the RAS-MAPK pathway), metabolic processes (NRF1 and SREBF1, associated with mTORC1 signaling), and chromatin remodeling (ZFP161, targeting of the repressive Polycomp complex).…”
Section: Discussionmentioning
confidence: 99%
“…Other prime TF candidates include TFs previously implicated in Tmem regulation such as RUNX3, E2F2, LEF1, BCL6, or members of the ELF-, KLF-, or FOXJ-families, as well as CREB1, ETS-1, and JUN-FOS, which are known to be involved in multiple cellular processes of differentiation and activation. Additional interesting candidates include (1) the aryl hydrocarbon receptor, AHR, which has been implicated in differentiation of CD4 + T cells into pro-or anti-inflammatory subsets and, hence, to modulate autoimmune diseases in various animal models (reviewed in Esser et al, 2009;Hanieh, 2014) and (2) the ets-family member FLI-1, which has been reported to affect thymic T cell development, TCR signaling, glycosphingolipid metabolism, and cytokine expression and has been implicated in autoimmune diseases, too (Richard et al, 2013;Sato et al, 2014). Others of the top-predicted TFs have not been directly associated to regulation of Tmem differentiation yet, but are players in potentially relevant cellular processes, such as intracellular signaling (RFX3, via the RAS-MAPK pathway), metabolic processes (NRF1 and SREBF1, associated with mTORC1 signaling), and chromatin remodeling (ZFP161, targeting of the repressive Polycomp complex).…”
Section: Discussionmentioning
confidence: 99%
“…MRL/lpr Fli1 +/+ immune cells, including T cells, do not readily migrate to the kidney when transferred into MRL/lpr Fli1 +/− mice (10). Chemokines Ccl2 ( Mcp-1 ), Ccl3 ( Mip-1α ), Ccl4 ( Mip-1β ) and Ccl5 ( Rantes ) are significantly decreased at the message level in the kidneys of MRL/lpr Fli1 +/− compared to Fli1 +/+ mice and FLI1 was demonstrated to regulate the promoter activity of several different cytokine genes in endothelial cells (8, 9, 12, 13). Here we demonstrated that the expression Cxcl9 and Cxcl10 , CXCR3 ligands, also are significantly decreased in the kidneys of MRL/lpr Fli1 +/− compared to the Fli1 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…6E sequence) and/or non-canonical ETS binding site that remains to be identified. The putative ETS sites in hCXCR3 tested for FLI1 binding were chosen based on numerous studies, including some from our laboratory, demonstrating that FLI1 binds and acts through conserved canonical ETS sites that are more proximal to the transcription start site (9, 12, 17, 3441). However, we recently demonstrated that FLI1 also can regulate promoters through more distal sites (12, 13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of the forward and reverse primers are listed in Table 1. The RT-PCR program has been previously desribed54. The threshold cycle (Ct) was calculated using the second-derivative maximum method and data were calculated via the delta−delta method.…”
Section: Methodsmentioning
confidence: 99%